EVALUATION OF KJELDAHL DIGESTION METHOD - Amin, M.; Flowers, T.H. (Journal of Research (Science), 2025)
The evaluation of the Kjeldahl digestion method was investigated by comparing measured values of total nitrogen, phosphorus and potassium using three salt and catalyst mixture in Standard Kjeldahl digestion method and Salicylic acid Modification method with certified values of plant material as well as comparison was made for determination of total nitrogen from steam distillation method verses the Technicon Auto-analyzer, and phosphorus Ascorbic acid/Molybdate method verses Molybdate/ Metavanadate method on the Technicon Auto-Analyzer. The 1 g salt/catalyst mixture recovered less nitrogen than the 2.5 g in the standard Kjeldahl method due to the lower temperature and incomplete digestion in both plant and soil samples. The 2.5 g catalyst mixture partially recovered nitrate in the standard Kjeldahl method and the salicylic acid modification fail to recover all nitrate in plant material. Use of 2.5 g salt catalyst mixture and selenium appears to promote nitrogen losses in salicylic acid modification method but not in the standard Kjeldahl method of digestion for soil samples. No interference of selenium or copper was observed in Nitrogen and Phosphorus on colorimetric determination. The standard kjeldahl method with 2.5 g of salt/catalyst mixture of sodium sulphate cupper sulphate (10:1) in 5 ml sulphuric acid were found suitable for determination of total Nitrogen, phosphorus and potassium. The steam distillation and the Technicon Auto-Analyzer technique measure similar amounts of ammonium nitrogen. However, the Technicon Auto analyzer technique is easier, rapid, high degree of reproducibility, precise, accurate, reliable and free from human error. The amount of phosphorus measured by the Ascorbic acid/Molybdate method was more accurate than by the Molybdate/ Metavanadate method on Technicon Auto-Analyzer.